2005
DOI: 10.1055/s-2004-826147
|View full text |Cite
|
Sign up to set email alerts
|

Ulcers and Gastritis

Abstract: This article reviews recently published reports on ulcers and gastritis. Helicobacter pylori is known to be an important pathogen involved in gastroduodenal inflammation and peptic ulcers. Conventional endoscopy is of limited usefulness in the evaluation of gastritis, but magnifying endoscopy is evidently helpful in the diagnosis of chronic atrophic gastritis, intestinal metaplasia, and H. pylori infection. A significant reduction in the incidence of refractory ulcers and the prevalence of H. pylori infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that H. pylori eradication sometimes induces gastroduodenal erosion and reflux esophagitis 20 . Sakaki reported that acute gastric erosion appeared in 7.9% of successfully eradicated cases 21 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that H. pylori eradication sometimes induces gastroduodenal erosion and reflux esophagitis 20 . Sakaki reported that acute gastric erosion appeared in 7.9% of successfully eradicated cases 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Long‐term Helicobacter pylori infection invariably leads to chronic gastritis [1]; it is a major cause of peptic ulcer [2] and a risk factor for gastric malignancies [3]. The natural course of infection with H. pylori is extremely variable.…”
mentioning
confidence: 99%
“…Thus, antacids, such as proton pump inhibitors (PPIs) and H 2 blockers, have been widely used to treat ARDs [ 4 , 5 ]. Although empirical treatment for ARDs primarily relies on conventional drugs, and the effects of H 2 -receptor antagonists and PPIs on the endoscopic improvement of acute and chronic gastritis have been reported [ 6 ], some patients may not respond well to these treatments [ 7 , 8 , 9 ]. Therefore, more effective medications are required to offer enhanced symptom relief for patients not experiencing sufficient symptom improvement with the existing therapeutic options.…”
Section: Introductionmentioning
confidence: 99%